Hypertension and blood pressure among meat eaters, fish eaters, vegetarians and vegans in EPIC-Oxford. - Appleby, P; Davey, G; Key, T (2002)
OBJECTIVE: To compare the prevalence of self-reported hypertension and mean systolic and diastolic blood pressures in four diet groups (meat eaters, fish eaters, vegetarians and vegans) and to investigate dietary and other lifestyle factors that might account for any differences observed between the groups. DESIGN: Analysis of cross-sectional data from participants in the Oxford cohort of the European Prospective Investigation into Cancer and Nutrition (EPIC-Oxford). SETTING: United Kingdom. SUBJECTS: Eleven thousand and four British men and women aged 20-78 years at blood pressure measurement. RESULTS: The age-adjusted prevalence of self-reported hypertension was significantly different between the four diet groups, ranging from 15.0% in male meat eaters to 5.8% in male vegans, and from 12.1% in female meat eaters to 7.7% in female vegans, with fish eaters and vegetarians having similar and intermediate prevalences. Mean systolic and diastolic blood pressures were significantly different between the four diet groups, with meat eaters having the highest values and vegans the lowest values. The differences in age-adjusted mean blood pressure between meat eaters and vegans among participants with no self-reported hypertension were 4.2 and 2.6 mmHg systolic and 2.8 and 1.7 mmHg diastolic for men and women, respectively. Much of the variation was attributable to differences in body mass index between the diet groups. CONCLUSIONS: Non-meat eaters, especially vegans, have a lower prevalence of hypertension and lower systolic and diastolic blood pressures than meat eaters, largely because of differences in body mass index.